2008
DOI: 10.1523/jneurosci.3192-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Endogenous Retinoids in the Molluscan CNS and Characterization of the Trophic and Tropic Actions of 9-cisRetinoic Acid on Isolated Neurons

Abstract: Retinoic acid (RA) is an active metabolite of Vitamin A that plays an important role in the growth and differentiation of many cell types. All-trans RA (atRA) is the retinoic acid isomer that has been most widely studied in the nervous system, and can induce and direct neurite outgrowth from both vertebrate and invertebrate preparations. The presence and role of the 9-cis-RA isomer in the nervous system is far less well defined. Here, we used high-pressure liquid chromatography (HPLC) and mass spectrometry (MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
41
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 62 publications
9
41
2
Order By: Relevance
“…However, the biological significance of 9-cis RA as the in vivo RXR ligand remains controversial as no significant levels of 9-cis RA could be detected in vivo in different vertebrates [130]. However, 9-cis RA was shown to be functional in other organisms, such as in the CNS of the mollusk Lymnaea stagnalis, where the presence of both all-trans RA and 9-cis RA has been shown [131]. Similarly, 9-cis RA was detected along with all-trans RA in locust embryos suggesting a functional role for retinoids in insects [132].…”
Section: Retinoid Receptor Ligandsmentioning
confidence: 99%
“…However, the biological significance of 9-cis RA as the in vivo RXR ligand remains controversial as no significant levels of 9-cis RA could be detected in vivo in different vertebrates [130]. However, 9-cis RA was shown to be functional in other organisms, such as in the CNS of the mollusk Lymnaea stagnalis, where the presence of both all-trans RA and 9-cis RA has been shown [131]. Similarly, 9-cis RA was detected along with all-trans RA in locust embryos suggesting a functional role for retinoids in insects [132].…”
Section: Retinoid Receptor Ligandsmentioning
confidence: 99%
“…There are no specific Ca 2ϩ channel blockers that are effective in Lymnaea neurons, so to this end, we used the general Ca 2ϩ channel blocker, cadmium, which has previously been shown to be effective in Lymnaea neurons (Feng et al, 2000;Dmetrichuk et al, 2008). Again, we monitored neurite outgrowth for 1 h after the addition of cadmium to the bath (10 Ϫ5 M, final concentration) and found that it had no adverse effect on the rate of neurite outgrowth (0.682 Ϯ 0.369 m/min; p Ͼ 0.05).…”
Section: Local Protein Synthesis Was Required For Ra-induced Growth Cmentioning
confidence: 99%
“…Retinoid extraction was performed as described previously (Dmetrichuk et al 2008). Briefly, tissue was thawed and homogenised in 500 μl of ice cold homogenisation buffer (phosphate buffered saline, pH 7.3 containing 0.5% ascorbic acid and 0.5% EDTA).…”
Section: Retinoid Extraction Proceduresmentioning
confidence: 99%
“…High-pressure liquid chromatography Techniques used were performed as described previously (Dmetrichuk et al 2008). Briefly, chromatographic separation was performed using a Waters Spherisorb S5ODS2 C-18 Column.…”
Section: Retinoid Extraction Proceduresmentioning
confidence: 99%
See 1 more Smart Citation